2020
DOI: 10.1186/s12884-020-03362-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of manual vacuum suction compared with conventional dilatation and sharp curettage and electric vacuum aspiration in surgical treatment of miscarriage: a randomized controlled trial

Abstract: Background The World Health Organization does not recommend dilatation and sharp curettage (D&C) for the surgical treatment of miscarriage during the first trimester because this may cause Asherman’s syndrome due to endometrial damage; therefore, suction remains the primary treatment option. While manual vacuum aspiration (MVA) has been widely used since the 1990s outside Japan, the use of an MVA device (Women’s MVA system) was approved in Japan in October 2015. Here, we examined the efficacy of the MVA ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 7 publications
2
25
0
Order By: Relevance
“…In another study, Azumaguchi et al [ 8 ] found a clear inverse relationship between endometrial thickness and previous D&C rates, suggesting that D&C is the primary cause of endometrial thinning [ 8 ]. In an evaluation performed before and after miscarriage surgery, our observation confirmed that there was no endometrial thinning when MVA was used [ 4 ]. MVA has a limited risk of endometrial damage and reduces the occurrence of Asherman’s syndrome and adenomyosis.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In another study, Azumaguchi et al [ 8 ] found a clear inverse relationship between endometrial thickness and previous D&C rates, suggesting that D&C is the primary cause of endometrial thinning [ 8 ]. In an evaluation performed before and after miscarriage surgery, our observation confirmed that there was no endometrial thinning when MVA was used [ 4 ]. MVA has a limited risk of endometrial damage and reduces the occurrence of Asherman’s syndrome and adenomyosis.…”
Section: Discussionsupporting
confidence: 61%
“…In October 2015, the Women’s MVA system was approved in Japan, and its use in the clinic has rapidly spread throughout Japan in recent years. In 2016, the MVA kit under general anesthesia was introduced at the hospital and has been used as a first-trimester pregnancy miscarriage surgical treatment, with its utility to date being reported [ 4 ]. The MVA kit is safe and effective and has a lower risk of endometrial damage, leading to a reduction of pain during and after the miscarriage surgery, thus simplifying anesthesia during the surgical procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports compared MVA with other surgical methods, 7,8 and in Japan, an RCT by Kakinuma et al showed that MVA safety was comparable with existing surgical techniques. 9 It was also reported that abortion surgery using curettage increases the risk of developing postoperative Asherman's syndrome compared with MVA. 10 Considering the WHO recommendations, 1 previous studies, and our survey results, MVA use for spontaneous miscarriage and induced abortion should be considered more in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] In Japan, an MVA kit (Women's MVA system MVA kit, Women's Health Japan) was approved in October 2015 and its use is becoming more widespread; the efficacy and safety of this MVA kit for miscarriages in the early stages of pregnancy have been reported previously. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%